Reconceptualizing Vulnerability: How Layers of Vulnerability Can Help Us Better Understand Medical Assistance in Dying - Manduca-Barone, Alessandro; Brassolotto, Julia; Waring, Duff (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
Medical assistance in dying (MAiD) was legalized in Canada in 2016. Since then, eligibility criteria have expanded through court challenges and legislation. During this expansion, there have been multiple reported cases that revealed individuals being offered or accessing MAiD due to a lack of other supports that may have otherwise ameliorated their suffering. As such, there have been renewed conversations about protecting the vulnerable. Here, we challenge the traditional subpopulation conception of vulnerability that treats persons as belonging to certain predefined subgroups. Instead, we support the more relational and contextual model of vulnerability as proposed by feminist bioethicist Florencia Luna. This conception views vulnerability as consisting of overlapping layers with cascading effects. We argue that such an approach is preferable both conceptually and practically and we apply it within the context of MAiD. This more nuanced approach to vulnerability can provide insight and guidance to governments and policy makers. Specifically, we consider three potential policy and practice recommendations that acknowledge and attempt to address the multiple ways in which patients might be rendered vulnerable: 1) an amendment to the Federal Government’s language about “protecting the vulnerable” in MAiD legislation; 2) enhanced MAiD assessments that better screen for social determinants of vulnerability and use a multidisciplinary approach to address them; and 3) establishing an oversight body consisting of members from multiple stakeholder groups with special expertise or experience relating to some of the most relevant sources of vulnerability.